2012
DOI: 10.1074/jbc.m111.324947
|View full text |Cite
|
Sign up to set email alerts
|

Human POLB Gene Is Mutated in High Percentage of Colorectal Tumors

Abstract: Background:Previous small scale studies indicate that DNA polymerase ␤ variants are present in 30% of human tumors. Results: 40% of samples in a large human colorectal tumor collection harbor coding region variants, many of which exhibit altered function. Conclusion: Aberrant activity or fidelity phenotypes exhibited by variants may contribute to tumorigenesis. Significance: Expression of variants in human tumors plays a role in driving carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 46 publications
3
92
0
Order By: Relevance
“…In an initial activity screen it was shown that G231D pol ␤ exhibits a slower rate of DNA synthesis compared with WT pol ␤ in the primer extension assay (24). Here, we show that G231D exhibits a slower catalytic rate compared with WT using the 45AG DNA substrate in pre-steady state burst assays (Table 1).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…In an initial activity screen it was shown that G231D pol ␤ exhibits a slower rate of DNA synthesis compared with WT pol ␤ in the primer extension assay (24). Here, we show that G231D exhibits a slower catalytic rate compared with WT using the 45AG DNA substrate in pre-steady state burst assays (Table 1).…”
Section: Resultsmentioning
confidence: 52%
“…The G231D variant of pol ␤ was identified in a colon tumor diagnosed as a stage 3 adenocarcinoma as described in the accompanying article (24). This variant was predicted to be damaging (24) and shown to catalyze DNA synthesis with a rate that is much lower than that of WT pol ␤.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pol ␤ extension activity in NCPs was normalized to the maximum extension activity by pol ␤ on the corresponding free DNA to account for sequence preferences. Normalized data from either assay were fitted to a single phase exponential curve using GraphPad Prism version 6 and the equation Y ϭ Y max (1 Ϫ e Ϫkobst ), as performed previously by others (32,45). The initial rate of extension by pol ␤ was calculated by multiplying k obs and the corresponding Y max values.…”
Section: Methodsmentioning
confidence: 99%
“…The E295K variant of pol ␤ was first identified in a gastric carcinoma and subsequently found by us in a colon carcinoma (21,22). Expression of the E295K variant in mouse mammary epithelial cells induces sister chromatid exchanges and cellular transformation (23).…”
Section: Dna Polymerases (Pol)mentioning
confidence: 99%